Declines in anogenital warts diagnoses since the change in 2012 to use the quadrivalent HPV vaccine in England: data to end 2017. (5th February 2019) - Checchi, Marta; Mesher, David; Mohammed, Hamish; Soldan, Kate
Abstract : Objectives: In 2008, a national human papillomavirus (HPV) vaccination programme for females was introduced in England using the bivalent vaccine (HPV16 and 18 only). In 2012, the programme changed to offer the quadrivalent vaccine that includes protection against the two HPV types that cause the majority of anogenital warts (AGW; HPV6 and 11). We present data reporting AGW diagnoses in sexual health clinics (SHCs) in England to the end of 2017, including diagnoses among birth cohorts offered the quadrivalent vaccine. Methods: Using data from all SHCs across England, we performed ecological analyses to consider rates of AGW diagnoses by age, gender and sexual orientation. We tested for trends over time of diagnoses of AGW in young females, heterosexual males, and men who have sex with men (MSM) between the ages of 15 and 24 years during both bivalent (2009 to 2013) and quadrivalent (2014 to 2017) vaccine time periods using Poisson regression. Results: Between 2014 and 2017, there was strong evidence for a decreasing trend in the rate of AGW diagnoses at SHC among females aged 15–17 years from 257.5 to 45.7 per 100 000 population (82.3% decline) and same aged heterosexual males from 59.1 to 19.1 per 100 000 population (67.7% decline). The reductions in the incidence of AGW diagnoses in MSM aged 15–17 years were less clear (decreased by 13.6% between 2014 and 2017, from 129.9 to 112.2 per 100 000 population). Conclusions: The moderate, unexpected declines in AGW seen since the introduction of a high-coverage HPV vaccination programme using the bivalent vaccine are being followed, as expected, by much larger declines among females offered the quadrivalent vaccine and same-aged heterosexual males. Surveillance plans are in place to continue to monitor AGW diagnoses to evaluate the impact of both female and targeted MSM HPV vaccination on early disease outcomes.